Dampak Kecemasan Atlet Pencak Silat Dalam Menghadapi Pertandingan Kategori Tanding - Fauzi Al Husen; Sri Maryati; Hendra Rustiawan (Jurnal Keolahragaan, 2024)
This study aims to determine the impact of anxiety experienced by pencak silat athletes of the Student Activity Unit (UKM) at Universitas Galuh when facing sparring competitions, as well as the strategies for overcoming it. Anxiety is a psychological condition commonly experienced by athletes before and during competitions, which can affect both their physical and mental performance. This research uses a qualitative approach with a case study method. Data were obtained through in-depth interviews, direct observation, and documentation involving eight active pencak silat athletes.The results show that anxiety affects both physiological and psychological aspects of athletes, such as increased heart rate, sleep disturbances, difficulty concentrating, and decreased self-confidence and performance during matches. Anxiety triggers include pressure from the audience, opponents perceived as superior, expectations from coaches, and past competition experiences. Nevertheless, some athletes were able to manage their anxiety effectively through strategies such as focusing on the match, positive thinking, intensive training, social support, and building self-confidence. These findings are expected to serve as a foundation for coaches and UKM trainers in designing effective psychological approaches to reduce anxiety and improve athlete performance optimally.  ABSTRAKPenelitian ini bertujuan untuk mengetahui dampak kecemasan yang dialami oleh atlet pencak silat Unit Kegiatan Mahasiswa (UKM) Universitas Galuh saat menghadapi pertandingan kategori tanding, serta strategi penyelesaiannya. Kecemasan merupakan kondisi psikologis yang umum dialami atlet sebelum dan saat bertanding, yang dapat mempengaruhi performa fisik maupun mental mereka. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data diperoleh melalui wawancara mendalam, observasi langsung, dan dokumentasi terhadap delapan atlet pencak silat yang aktif bertanding. Hasil penelitian menunjukkan bahwa kecemasan berdampak pada aspek fisiologis dan psikologis atlet, seperti detak jantung meningkat, gangguan tidur, kesulitan konsentrasi, serta menurunnya rasa percaya diri dan performa saat bertanding. Faktor pemicu kecemasan meliputi tekanan dari penonton, lawan yang dianggap lebih unggul, ekspektasi dari pelatih, dan pengalaman bertanding sebelumnya. Meski demikian, sebagian atlet mampu mengelola kecemasan dengan baik melalui strategi seperti fokus pada pertandingan, berpikir positif, latihan intensif, dukungan sosial, dan membangun kepercayaan diri. Temuan ini diharapkan dapat menjadi dasar bagi pelatih dan pembina UKM dalam merancang pendekatan psikologis yang efektif untuk mengurangi kecemasan dan meningkatkan performa atlet secara optimal.